Adolescent self-efficacy and attitude towards HIV AIDS prevention in Yogyakarta, Indonesia - Niken Meilani; Nanik Setiyawati; Sammy Barasa (Poltekkes Kemenkes Yogyakarta, 2022)
Acquired Immunodeficiency Syndrome (AIDS) was the eighth leading cause of death among adolescents worldwide. A third of these were infected during adolescence period. HIV prevention in adolescents is particularly important. Attitude is one indicator of a person's behavior or action. This study aimed to establish the determinants of adolescents’ attitudes toward the prevention of HIV AIDS among adolescents. This was a descriptive cross-sectional study conducted among 370 high school students in Yogyakarta, Indonesia. Quantitative data was analyzed using SPSS and involved univariate and multivariate analysis. The result of this study showed that the internet and television were the major sources of information on reproductive health and HIV among adolescents (98.9%) and (98.4%) respectively. The determinant factors of adolescents' attitude towards HIV/AIDS prevention were the level of knowledge (p=0.028) and self-efficacy (p=0.007) and multivariate analysis showed respondents with positive self-efficacy were 1.8 times more likely to have a positive attitude towards HIV/AIDS prevention. The conclusion is self-efficacy is a determinant factor in attitude. The recommendation of this study is to stakeholders on interventions that can improve adolescents' self-efficacy to achieve HIV prevention goals.